HUBUNGAN ANTARA FASILITAS BELAJAR DIRUMAH DAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR PEKERJAAN DASAR OTOMOTIF KELAS X SMK MUHAMMADIYAH 2 SLEMAN: Hubungan, fasilitas belajar, motivasi belajar, prestasi belajar - setiawanawan323 Awan setiawan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine: (1) the positive relationship between learning facilities and learning achievement of Basic Automotive Work of TKR students at SMK Muhamadiyah 2 Sleman. (2) There is a positive relationship between learning facilities at home and learning motivation with learning achievement of Basic Automotive Jobs for TKR students at SMK Muhamadiyah 2 Sleman. This type of research is ex-post facto. As for the method used is correlational. The population of this research is the students of class X TKR SMK Muhammadiyah 2 Sleman as many as 63 students. The sample selection technique used proportional random sampling with a total of 25 students. Collecting data using questionnaires and documentation. The data analysis technique used was partial correlation and multiple correlation analysis. The results of this study (1) there is a positive and significant relationship between learning facilities at home and learning achievement for basic automotive engineering R Square of 0.801. (2) there is a positive and significant relationship between learning motivation and learning achievement of basic automotive engineering students at SMK Muhammadiyah 2 Sleman.